Offshore Spreading of a Supercritical Plume Under Upwelling Wind Forcing: A Case Study of the Winyah Bay Outflow - Yankovsky, Alexander E.; Fribance, Diane B.; Cahl, Douglas; Voulgaris, George (Frontiers in Marine Science, 2022)
In this study, we present observations of the Winyah Bay (WB) plume (SC, United States) formed by high freshwater discharge and a moderate upwelling-favorable wind acting continuously for ∼1.5 days prior to the shipboard survey. If a similar wind forcing persists over a longer period, the plume turns upstream (against its natural propagation) and curves offshore forming a “filament” with minimal transverse spreading, as seen in numerous satellite images. The observed plume comprises a train of tidal sub-plumes undergoing rotational adjustment and being transported offshore by Ekman dynamics. The WB outflow is supercritical in terms of the interior Froude number. Moderate wind extends this supercritical regime farther offshore. The plume is characterized by interior fronts associated with consecutive tidal pulses. Age of the buoyant water can be distinguished by the buoyant layer mixing (evident in the layer’s thickness and salinity anomaly) along with the transformation of its TS properties. However, relatively little transverse (lateral) spreading of buoyant water occurs: the equivalent freshwater layer thickness remains surprisingly consistent, approximately 0.8 m, over more than 20 km in the direction of the bulge extension. It is hypothesized that the supercritical regime constrains the transverse spreading of a plume. Microstructure measurements reveal higher dissipation rates below the base of the older (offshore) part of the plume. This is attributed to internal wave radiation from a newly discharged tidal pulse into an older plume, with the buoyant layer acting as a waveguide. Theoretical estimations of the internal wave properties show that the interior front is highly supercritical, while the observed dissipation maximum agrees with the theoretical wave structure.